Intermediaries in International Conflict - Thomas Princen (Princeton University Press, 2014)
THIS STUDY began in the early 1980s with what seemed like fairly straightforward questions. What is this newly rediscovered method of peacemaking called mediation? Is it yet one more tool in the diplomat s bag of tricks—a variation on negotiation—or is there something distinctive about the process and the people who do it? What, in practice, does it actually look like and feel like? Are mediators born or trained? How useful is it in promoting peaceful means of resolving conflicts? Now, one decade later, although a few patterns and propositions have emerged, the questions only seem to have multiplied. But such is the nature of social science research, especially that in the realm of decision making and policy. One asks questions, begins to get what seems like answers, and then discovers yet more questions. There is no end, no "theory" on the order of relativity or natural selection. But everyone wants to affect policy, to put in one's two bits worth to make the world a little better. So what follows is admittedly tentative, certainly deserving of further theoretical and empirical exploration. The questions and propositions about intermediary intervention were largely spurred by the recollections of those who have done it. Initially, conversations with two pioneers in domestic environmental mediation— Gerald Cormick and James Arthur—aroused my curiosity. At the international level, Herbert Kelman introduced me to prenegotiations through two of his intensive, problem-solving workshops with Israelis and Palestinians. An anonymous Vatican official who, by spending six years of his ecclesiastical life mediating a dispute over a few obscure islands at the tip of South America and is, therefore, credibly able to claim to be among the most experienced international mediators living, granted me a series of extensive interviews. These revealed what the official accounts and press releases could not: the actual practice of international mediation, the daily grind, the frustrations, the risks, and, in this case, the fleeting glory of a successful outcome. Adam Curie and Joseph Elder, two Quaker mediators with extensive experience in Africa and Asia, acquainted me with a brand of diplomacy recognized by few but valued highly by those entangled in intractable conflicts. Finally, many who sat at one end of the negotiating table or the other shared their insights into the opportunities and the constraints of international mediation. It is from the experience, determination, and wisdom of these practitioners that this book owes its greatest debt and from which I feel most humble as I try to capture the essence of their peacemaking efforts.